Effect of Thermal Stress on Urine Specific Gravity, Blood Pressure, and Heartbeat Among Underground Miners (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Underground miners highly exposed to thermal stress hazard. Closed condition, heavy work load, and limited ventilation are the common cause of high environment temperature in underground mining. Thermal stress can influence metabolism and physiological function of human body. The objective of these study is to investigate the effect of thermal stress to physiological (bodyweight, blood pressure, urine specific gravity, and heartbeat) of underground miners. This study is observational cross sectional study with 42 underground miners. Thermal stress level is 147.14 Wm2 and categorized as unrestricted zone. These study showed that urine specific gravity, blood pressure, and heart beat on underground miners were change after shift work, while the body weight changes were not observed. The relation among TWL with blood pressure, urine specific gravity, and heartbeat is low category.